1988
DOI: 10.1063/1.340823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on grain-boundary microstructure in Nd-Fe-B sintered magnet

Abstract: Microstructure of grain-boundary regions in sintered Nd15Fe77B8 magnets has been observed under a high-resolution TEM. Crystalline Nd-rich phase is not observed at all the grain boundaries, while amorphouslike layers are observed quite often. It has also been found that no bcc phase in as-sintered samples was observed before heating the samples but heating of the samples for annealing has caused bcc microcrystals to form in the edges of the matrix phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Sm-Co, L1 0 CoPt, Nd-Fe-B, MnBi) are sensitive to thermal processing conditions [298,302,310,311,327,332], which leads to many challenges in achieving and retaining a high energy density. For instance, a high temperature anneal around 600 • C is known to obtain a high coercivity in sintered Nd-Fe-B magnets [326,331], while a magnetic field anneal can induce a preferred orientation of the crystal [307]. It is also known that upon rapid thermal annealing of Sm-Co/Co multilayered films at 525 • C, an exchange-coupled, single-phase magnet can be obtained with a large energy product [332].…”
Section: Discussionmentioning
confidence: 99%
“…Sm-Co, L1 0 CoPt, Nd-Fe-B, MnBi) are sensitive to thermal processing conditions [298,302,310,311,327,332], which leads to many challenges in achieving and retaining a high energy density. For instance, a high temperature anneal around 600 • C is known to obtain a high coercivity in sintered Nd-Fe-B magnets [326,331], while a magnetic field anneal can induce a preferred orientation of the crystal [307]. It is also known that upon rapid thermal annealing of Sm-Co/Co multilayered films at 525 • C, an exchange-coupled, single-phase magnet can be obtained with a large energy product [332].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the coercivity of Nd-Fe-B sintered magnets was structure sensitive and dependent on the distribution of Nd-rich phases [3], the distribution of misaligned grains [4], average grain size and size distribution [5]. It has been known that heat-treatment processes greatly affect the structure of the sintered magnet [6][7][8], in particular on the distribution of Nd-rich phases.…”
Section: Introductionmentioning
confidence: 99%
“…Permite a obtenção de regiões suficientemente finas para observação, más também pode gerar alguns inconvenientes já comentados anteriormente na literatura. Tsubokawa et al (1988) relataram num estudo investigando o contorno de grão, que a oxidação e o bombardeamento de íons causam aquecimento local durante o processo de preparação de amostras e modificam a estrutura cristalográfica numa faixa de ~ 20nm junto a fase matriz.…”
Section: -Sistema De Polimento Iônico De Precisãounclassified
“…O contraste gerado nas imagens com baixa magnificação indica a presença de uma camada de isolação entre os grãos conforme ilustra a FIG. 4.4 Os contornos localizados no ímã de composição Pr 15 Fe bal Co 8 B 7 Nb 0,05 Ga 0,25 são contínuos e regulares em toda a extensão, embora tenham sido observadas modificações nas vizinhanças da camada de isolação numa faixa de cerca de 20 nm provavelmente devido a danos causados pelo polimento iônico (Tsubokawa et al,1988). Analises realizadas com ímãs de NdFeB revelaram modificações na estrutura próxima aos contornos devido ao aquecimento causado pelo bombardeamento iônico do "íon milling" e sugerem eventualmente o uso de nitrogênio líquido durante o processo de polimento ).…”
Section: -Estudo Dos Contornos De Grãosunclassified